(untitled) (MMIT Proceedings, 2024)
In this article, the author analyses the pedagogical ideas of Sri Aurobindo Ghosh, a notable representative of Indian philosophy in the 20th century. The author also examines the significance of these ideas for the modern educational system. According to the author, Aurobindo’s concept of integral pedagogy occupies a special place in the development of spiritual values among younger generations.